Multiple cryptic lineages and restricted gene flow in the decorator worm Diopatra Cuprea - Adam J. Ziegler; Tina M. Bell; Sarah K. Berke; Allan E. Strand; Erik E. Sotka (Marine Biology, 2025)
The decorator worm Diopatra cuprea Bosc, 1802 (Annelid; Polycheate; Onuphidae) is an ecosystem engineer within high-salinity estuaries of the southern and eastern United States. A previous study revealed five morphologically cryptic mitochondrial lineages across its broad geographic distribution. Here, we explore mitonuclear concordance of these lineages using single nucleotide polymorphisms (SNPs) genotyped with RADseq. We genotyped 3,162 SNPs from 233 D. cuprea and detected four deep lineages in the nuclear genome: a northern US clade (Massachusetts), a single nuclear clade within mid-Atlantic populations (i.e., Virginia south through northeastern Florida), a southeastern Florida clade, and a Gulf of Mexico clade. There was mitonuclear concordance within most individuals for three lineages, while two mitochondrial lineages were detected in a single mid-Atlantic nuclear lineage. Thus, there appear to be four cryptic lineages of D. cuprea that suggest four distinct species that rarely hybridize. Within the mid-Atlantic lineage, we detected increasing genetic isolation of populations with increasing geographic distance, a pattern consistent with low dispersal of D. cuprea larvae. Cryptic diversity within the D. cuprea complex is consistent with other common and geographically widespread annelid and Diopatra species that are now being revealed using high-throughput sequencing.

Integrative demographic modelling reduces uncertainty in estimated rates of species' historical range shifts - Antonio R. Castilla; Alissa Brown; Sean Hoban; Everett Andrew Abhainn; John D. Robinson; Jeanne Romero‐Severson; Adam B. Smith; Allan E. Strand; John R. Tipton; Andria Dawson (Journal of Biogeography, 2024)
Aim Biogeographers have used three primary data types to examine shifts in tree ranges in response to past climate change: fossil pollen, genetic data and contemporary occurrences. Although recent efforts have explored formal integration of these types of data, we have limited understanding of how integration affects estimates of range shift rates and their uncertainty. We compared estimates of biotic velocity (i.e. rate of species' range shifts) using each data type independently to estimates obtained using integrated models. Location Eastern North America. Taxon Fraxinus pennsylvanica Marshall (green ash). Methods Using fossil pollen, genomic data and modern occurrence data, we estimated biotic velocities directly from 24 species distribution models (SDMs) and 200 pollen surfaces created with a novel Bayesian spatio‐temporal model. We compared biotic velocity from these analyses to estimates based on coupled demographic‐coalescent simulations and Approximate Bayesian Computation that combined fossil pollen and SDMs with population genomic data collected across the F. pennsylvanica range. Results Patterns and magnitude of biotic velocity over time varied by the method used to estimate past range dynamics. Estimates based on fossil pollen yielded the highest rates of range movement. Overall, integrating genetic data with other data types in our simulation‐based framework reduced apparent uncertainty in biotic velocity estimates and resulted in greater similarity in estimates between SDM‐ and pollen‐integrated analyses. Main Conclusions By reducing uncertainty in our assessments of range shifts, integration of data types improves our understanding of the past distribution of species. Based on these results, we propose further steps to reach the integration of these three lines of biogeographical evidence into a unified analytical framework.

Latitudinally distinct stocks of Atlantic cod face fundamentally different biophysical challenges under on‐going climate change - Olav Sigurd Kjesbu; Maud Alix; Anne Britt Sandø; Espen Strand; Peter J. Wright; David G. Johns; Anders Thorsen; C. Tara Marshall; Kjell Gunnar Bakkeplass; Frode B. Vikebø; Mari Skuggedal Myksvoll; Geir Ottersen; et al. (Fish and Fisheries, 2023)
The reproductive success of marine ectotherms is especially vulnerable in warming oceans due to alterations in adult physiology, as well as embryonic and larval survival prospects. These vital responses may, however, differ considerably across the species' geographical distribution. Here we investigated the life history, focusing on reproductive ecology, of three spatially distant populations (stocks) of Atlantic cod ( Gadus morhua , Gadidae) (50–80° N), in the Irish/Celtic Seas‐English Channel Complex, North and Barents Seas, under past and projected climate. First, experimental tracking of spawning behaviour evidenced that the ovulation cycle is highly distressed at ≥9.6 (±0.25)°C ( T up ). This knife‐edge threshold resulted in erratic spawning frequencies, whereas vitellogenin sequestration remained unaffected, indicating endocrine rather than aerobic scope constraints. Cod in the Celtic Sea‐English Channel are, therefore, expected to show critical stock depensation over the next decades as spawning grounds warm above T up , with Irish Sea cod subsequently at risk. Second, in the relatively cooler North Sea, the northward retraction of Calanus finmarchicus (Calanidae) and Para‐Pseudocalanus spp. (Clausocalanidae) (1958–2017) limit cod larvae feeding opportunities, particularly in the southernmost subarea. However, the contrasting increase in Calanus helgolandicus (Calanidae) does not counteract this negative effect, likely because cod larvae hatch ahead of its abundance peaks. Overfishing again comes as a twin effect. Third, in the still relatively cold Barents Sea, the sustainably harvested cod benefit from improved food conditions in the recent ice‐free polar region but at the energetic cost of lengthier and faster spawning migrations. Consequently, under climate change local stocks are stressed by different mechanistic factors of varying management severity.

Diversity, divergence and density: How habitat and hybrid zone dynamics maintain a genomic cline in an intertidal barnacle - John P. Wares; Allan E. Strand; Erik E. Sotka (Journal of Biogeography, 2021)
Aim As within‐species genomic data have been shown useful in interpreting broader biogeographic trends, we analysed the mode of population genomic isolation involved in a well‐studied intertidal genomic cline to better understand the mechanisms maintaining it. These results were interpreted in the context of spatial variation in habitat use and availability as well as likely fitness consequences for hybridization between the two lineages. Location Pacific coast of North America. Taxon Arthropods (Class Maxillopoda, Order Sessilia, Family Balanidae; Balanus glandula ). Methods Genotype‐by‐sequencing approaches were used to generate single‐nucleotide polymorphism markers across sites sampled between southern Alaska and Southern California. Inference using standard population genomic methods, including analysis of population structure, inbreeding and linkage disequilibrium, was used to identify the steepest transitions across the largest number of loci examined. These data were put in the context of observed population density and habitat availability. Results We show that the majority of markers analysed show strong clinal transitions in a very narrow portion of the California coast. Patterns of linkage disequilibrium among markers, along with prior evidence of variation in reproductive potential by latitude and by mitochondrial lineage, suggest some reproductive isolation among the northern and southern lineages of B. glandula that are concordant with the drop in population density and habitat availability in central California. Main Conclusions A significant clinal transition in genomic diversity is stronger and more localized than previously recognized and exhibits statistical patterns suggesting that the lineages are reproductively and phenotypically distinct in ways that may be ecologically important. As this species has been used to infer process in coastal biogeography, further study of concordant patterns will be important for advancing our understanding of this region.

Founder effects shape linkage disequilibrium and genomic diversity of a partially clonal invader - Ben A. Flanagan; Stacy A. Krueger‐Hadfield; Courtney J. Murren; Chris C. Nice; Allan E. Strand; Erik E. Sotka (Molecular Ecology, 2021)
The genomic variation of an invasive species may be affected by complex demographic histories and evolutionary changes during the invasion. Here, we describe the relative influence of bottlenecks, clonality, and population expansion in determining genomic variability of the widespread red macroalga Agarophyton vermiculophyllum . Its introduction from mainland Japan to the estuaries of North America and Europe coincided with shifts from predominantly sexual to partially clonal reproduction and rapid adaptive evolution. A survey of 62,285 SNPs for 351 individuals from 35 populations, aligned to 24 chromosome‐length scaffolds indicate that linkage disequilibrium (LD), observed heterozygosity ( H o ), Tajima's D, and nucleotide diversity (Pi) were greater among non‐native than native populations. Evolutionary simulations indicate LD and Tajima's D were consistent with a severe population bottleneck. Also, the increased rate of clonal reproduction in the non‐native range could not have produced the observed patterns by itself but may have magnified the bottleneck effect on LD. Elevated marker diversity in the genetic source populations could have contributed to the increased H o and Pi observed in the non‐native range. We refined the previous invasion source region to a ~50 km section of northeastern Honshu Island. Outlier detection methods failed to reveal any consistently differentiated loci shared among invaded regions, probably because of the complex A. vermiculophyllum demographic history. Our results reinforce the importance of demographic history, specifically founder effects, in driving genomic variation of invasive populations, even when localized adaptive evolution and reproductive system shifts are observed.

Explaining the worldwide distributions of two highly mobile species: Cakile edentula and Cakile maritima - Elliot C. Shaw; Rachael Fowler; Sara Ohadi; Michael J. Bayly; Rosemary A. Barrett; Josquin Tibbits; Allan Strand; Charles G. Willis; Kathleen Donohue; Philipp Robeck; Roger D. Cousens (Journal of Biogeography, 2021)
Aim If we are able to determine the geographic origin of an invasion, as well as its known area of introduction, we can better appreciate the innate environmental tolerance of a species and the strength of selection for adaptation that colonizing populations have undergone. It also enables us to maximize the success of searches for effective biological control agents. We determined the number of successful colonization events that have occurred throughout the world for two Cakile species and compared the climates from which they originated, in which they established and then spread. Location Worldwide. Taxon Sea‐Rockets ( Cakile spp.), Brassicaceae. Methods We used a high‐throughput sequencing and a genome skimming approach combined with Bayesian Inference phylogenetics to examine variation in entire chloroplast genomes and regions of nuclear ribosomal DNA within native and introduced areas. Databases were used to compare climates between native ranges and introduced regions for multiple clades within each species. Results At least seven clades have invaded different regions of the world. In most cases we were able to identify their source regions and climates. The environmental bottlenecks differed in intensity: while some clades colonized into climates that were similar to climates in their native range, other clades had a very broad innate environmental tolerance such that new invasions succeeded beyond the climate range of native populations. We found clear evidence of hybridization—specifically, chloroplast capture—between two species in Australia. Conclusions Results here show that these species are sometimes capable of colonizing in climates that are beyond the climate range of native populations. Whether successful colonization beyond native climate niches requires de novo adaptation, or whether it represents an innate broad fundamental niche requires further investigation. Cakile species provide an excellent opportunity to study replicated climate adaptation trajectories.

Disrupting the disruptors: the consequences of mutations in mobile elements for ecologically important life history traits - Matthew T. Rutter; April M. Bisner; Clare Kohler; Keyaira Morgan; Olivia Musselman; Julia Pickel; Jerica Tan; Yuki Yamasaki; Jay Willson; Hilary S. Callahan; Allan E. Strand; Courtney J. Murren (Evolutionary Ecology, 2020)

When and where plant‐soil feedback may promote plant coexistence: a meta‐analysis - Kerri M. Crawford; Jonathan T. Bauer; Liza S. Comita; Maarten B. Eppinga; Daniel J. Johnson; Scott A. Mangan; Simon A. Queenborough; Allan E. Strand; Katharine N. Suding; James Umbanhowar; James D. Bever (Ecology Letters, 2019)
Plant‐soil feedback (PSF) theory provides a powerful framework for understanding plant dynamics by integrating growth assays into predictions of whether soil communities stabilise plant–plant interactions. However, we lack a comprehensive view of the likelihood of feedback‐driven coexistence, partly because of a failure to analyse pairwise PSF, the metric directly linked to plant species coexistence. Here, we determine the relative importance of plant evolutionary history, traits, and environmental factors for coexistence through PSF using a meta‐analysis of 1038 pairwise PSF measures. Consistent with eco‐evolutionary predictions, feedback is more likely to mediate coexistence for pairs of plant species (1) associating with similar guilds of mycorrhizal fungi, (2) of increasing phylogenetic distance, and (3) interacting with native microbes. We also found evidence for a primary role of pathogens in feedback‐mediated coexistence. By combining results over several independent studies, our results confirm that PSF may play a key role in plant species coexistence, species invasion, and the phylogenetic diversification of plant communities.

Forecasting the genetic influences of red drum stock enhancement in South Carolina - Christopher J. Katalinas; John D. Robinson; Allan E. Strand; Tanya Darden; Karl Brenkert; Michael R. Denson (Fisheries Management and Ecology, 2019)
The South Carolina Department of Natural Resources ( SCDNR ) began stocking red drum, Sciaenops ocellatus (Linnaeus), in 1989 to augment the abundance of juveniles available for recreational harvest in South Carolina estuaries. While stock enhancement can help supplement wild populations under high fishing pressure, releasing hatchery‐raised fish into the wild also presents the risk of decreased genetic diversity. An individual‐based model ( IBM ) was developed to forecast the genetic influences of stocking on the wild spawning population to inform responsible stocking strategies. Model results indicated the SCDNR red drum stock enhancement programme should maintain mean contributions of stocked fish no greater than 30% per year class over a 45‐year stocking period, coupled with at least 10 effective breeders in the hatchery replaced annually, to maintain current levels of genetic diversity estimated in the wild population. The IBM is a useful tool for hatchery managers to guide responsible stock enhancement.

Invasion of novel habitats uncouples haplo‐diplontic life cycles - Stacy A. Krueger‐Hadfield; Nicole M. Kollars; James E. Byers; Thomas W. Greig; Mareike Hammann; David C. Murray; Courtney J. Murren; Allan E. Strand; Ryuta Terada; Florian Weinberger; Erik E. Sotka (Molecular Ecology, 2016)
Baker's Law predicts uniparental reproduction will facilitate colonization success in novel habitats. While evidence supports this prediction among colonizing plants and animals, few studies have investigated shifts in reproductive mode in haplo‐diplontic species in which both prolonged haploid and diploid stages separate meiosis and fertilization in time and space. Due to this separation, asexual reproduction can yield the dominance of one of the ploidy stages in colonizing populations. We tested for shifts in ploidy and reproductive mode across native and introduced populations of the red seaweed Gracilaria vermiculophylla . Native populations in the northwest Pacific Ocean were nearly always attached by holdfasts to hard substrata and, as is characteristic of the genus, haploid–diploid ratios were slightly diploid‐biased. In contrast, along North American and European coastlines, introduced populations nearly always floated atop soft‐sediment mudflats and were overwhelmingly dominated by diploid thalli without holdfasts. Introduced populations exhibited population genetic signals consistent with extensive vegetative fragmentation, while native populations did not. Thus, the ecological shift from attached to unattached thalli, ostensibly necessitated by the invasion of soft‐sediment habitats, correlated with shifts from sexual to asexual reproduction and slight to strong diploid bias. We extend Baker's Law by predicting other colonizing haplo‐diplontic species will show similar increases in asexuality that correlate with the dominance of one ploidy stage. Labile mating systems likely facilitate colonization success and subsequent range expansion, but for haplo‐diplontic species, the long‐term eco‐evolutionary impacts will depend on which ploidy stage is lost and the degree to which asexual reproduction is canalized.

Genetic structure along the strandline: Unravelling invasion history in a one‐dimensional system - Sara Ohadi; Peter K. Ades; Rebecca Ford; Allan E. Strand; Josquin Tibbits; Mohsen B. Mesgaran; Roger D. Cousens (Journal of Biogeography, 2016)
Aim To unravel the genetic processes involved in a case of invasion by one species, the self‐incompatible Cakile maritima Scop. (Brassicaceae) in Australia, as it has replaced a related prior invader, Cakile edentula (Bigelow) Hook. Location Southern and eastern coastlines of Australia. Methods Genetic diversity within and between populations was characterized at a continental scale using microsatellite ( SSR ) markers to examine nuclear diversity and cleaved amplified polymorphic sequence ( CAPS ) markers to examine chloroplasts. DNA was sourced from 24 populations of C. maritima along its putative invasion trajectory and, for comparison, from four populations of C. edentula that are currently being invaded by C. maritima . Analysis of Molecular Variance and a Bayesian assignment method were used to explore the data. Results No evidence was found for progressive loss of diversity in C. maritima in the putative direction of range expansion. Western and south‐eastern populations of C. maritima have almost certainly resulted from independent introductions, although there is evidence of very limited gene flow from west to east. There was considerably greater, spatially structured variation in the south‐east, suggesting multiple introductions of C. maritima to that region. We found evidence of hybridization and introgression from C. edentula into C. maritima , both in the two regions where they are currently sympatric and elsewhere. Main conclusions The invasion history of a species spreading in a largely one‐dimensional habitat can still be highly complex and difficult to interpret. Regional patterns of variation in C. maritima indicate several introductions from different parts of the native range, limited gene flow from the first introduction eastwards and genetic drift within Western Australia. There has also been bi‐directional gene flow between this species and C. edentula . The significance of the introgression from C. edentula into C. maritima with respect to natural selection, however, remains to be determined.

Long‐term dynamics of mycorrhizal root tips in a loblolly pine forest grown with free‐air CO 2 enrichment and soil N fertilization for 6 years - Seth G. Pritchard; Benton N. Taylor; Emily R. Cooper; Katilyn V. Beidler; Allan E. Strand; M. Luke McCormack; Siyao Zhang (Global Change Biology, 2014)
Large‐scale, long‐term FACE (Free‐Air CO 2 enrichment) experiments indicate that increases in atmospheric CO 2 concentrations will influence forest C cycling in unpredictable ways. It has been recently suggested that responses of mycorrhizal fungi could determine whether forest net primary productivity ( NPP ) is increased by elevated CO 2 over long time periods and if forests soils will function as sources or sinks of C in the future. We studied the dynamic responses of ectomycorrhizae to N fertilization and atmospheric CO 2 enrichment at the Duke FACE experiment using minirhizotrons over a 6 year period (2005–2010). Stimulation of mycorrhizal production by elevated CO 2 was observed during only 1 (2007) of 6 years. This increased the standing crop of mycorrhizal tips during 2007 and 2008; during 2008, significantly higher mortality returned standing crop to ambient levels for the remainder of the experiment. It is therefore unlikely that increased production of mycorrhizal tips can explain the lack of progressive nitrogen limitations and associated increases in N uptake observed in CO 2 ‐enriched plots at this site. Fertilization generally decreased tree reliance on mycorrhizae as tip production declined with the addition of nitrogen as has been shown in many other studies. Annual NPP of mycorrhizal tips was greatest during years with warm January temperatures and during years with cool spring temperatures. A 2 °C increase in average late spring temperatures (May and June) decreased annual production of mycorrhizal root tip length by 50%. This has important implications for ecosystem function in a warmer world in addition to potential for forest soils to sequester atmospheric C.

Improved scaling of minirhizotron data using an empirically-derived depth of field and correcting for the underestimation of root diameters - Benton N. Taylor; Katilyn V. Beidler; Allan E. Strand; Seth G. Pritchard (Plant and Soil, 2014)

Sampling volume in root studies: the pitfalls of under‐sampling exposed using accumulation curves - Benton N. Taylor; Katilyn V. Beidler; Emily R. Cooper; Allan E. Strand; Seth G. Pritchard (Ecology Letters, 2013)
Root systems are important for global models of below‐ground carbon and nutrient cycling. Notoriously difficult sampling methods and the fractal distribution of root diameters in the soil make data being used in these models especially susceptible to error resulting from under‐sampling. We applied the concept of species accumulation curves to root data to quantify the extent of under‐sampling inherent to minirhizotron and soil coring sampling for both root uptake and carbon content studies. Based on differences in sample size alone, minirhizotron sampling missed approximately one third of the root diameters observed by soil core sampling. Sample volumes needed to encounter 90% of root diameters averaged 2481 cm 3 for uptake studies and 5878 cm 3 for root carbon content studies. These results show that small sample volumes encounter a non‐representative sample of the overall root pool, and provide future guidelines for determining optimal sample volumes in root studies.

Insights on common dolphin (Delphinus delphis) social organization from genetic analysis of a mass-stranded pod - Amélia Viricel; Allan E. Strand; Patricia E. Rosel; Vincent Ridoux; Pascale Garcia (Behavioral Ecology and Sociobiology, 2008)

Fine root dynamics in a loblolly pine forest are influenced by free‐air‐CO 2 ‐enrichment: a six‐year‐minirhizotron study - SETH G. PRITCHARD; ALLAN E. STRAND; M. LUKE McCORMACK; MICHEAL A. DAVIS; ADRIEN C. FINZI; ROBERT B. JACKSON; ROSER MATAMALA; HUGO H. ROGERS; RAM OREN (Global Change Biology, 2008)
Efforts to characterize carbon (C) cycling among atmosphere, forest canopy, and soil C pools are hindered by poorly quantified fine root dynamics. We characterized the influence of free‐air‐CO 2 ‐enrichment (ambient +200 ppm) on fine roots for a period of 6 years (Autumn 1998 through Autumn 2004) in an 18‐year‐old loblolly pine ( Pinus taeda ) plantation near Durham, NC, USA using minirhizotrons. Root production and mortality were synchronous processes that peaked most years during spring and early summer. Seasonality of fine root production and mortality was not influenced by atmospheric CO 2 availability. Averaged over all 6 years of the study, CO 2 enrichment increased average fine root standing crop (+23%), annual root length production (+25%), and annual root length mortality (+36%). Larger increase in mortality compared with production with CO 2 enrichment is explained by shorter average fine root lifespans in elevated plots (500 days) compared with controls (574 days). The effects of CO 2 ‐enrichment on fine root proliferation tended to shift from shallow (0–15 cm) to deeper soil depths (15–30) with increasing duration of the study. Diameters of fine roots were initially increased by CO 2 ‐enrichment but this effect diminished over time. Averaged over 6 years, annual fine root NPP was estimated to be 163 g dw m −2 yr −1 in CO 2 ‐enriched plots and 130 g dw m −2 yr −1 in control plots ( P = 0.13) corresponding to an average annual additional input of fine root biomass to soil of 33 g m −2 yr −1 in CO 2 ‐enriched plots. A lack of consistent CO 2 × year effects suggest that the positive effects of CO 2 enrichment on fine root growth persisted 6 years following minirhizotron tube installation (8 years following initiation of the CO 2 fumigation). Although CO 2 ‐enrichment contributed to extra flow of C into soil in this experiment, the magnitude of the effect was small suggesting only modest potential for fine root processes to directly contribute to soil C storage in south‐eastern pine forests.